LEADERSHIP'S FUNCTION IN ENCOURAGING WOMEN'S FARMING GROUPS TO REDUCE FOOD INSECURITY AND ITS RELATION TO ISLAMIC AGRICULTURE - FISY AMALIA; EKO CAHYO MAYNDARTO; FARHAAN PRIYADI; JIDAN DWILAKSANA; KHOIRUL ANAM (Universitas Islam Negeri Imam Bonjol Padang, 2021)
This study aims to identify the leadership factors by the Theory of Transformational Leadership that have contributed to the success of a group of female farmers in Buaran, Serpong, Tangerang Selatan, Indonesia, known as Az Zahra. The data were collected using both primary and secondary sources, and the methodologies used were qualitative. Officials, supervisors, and group members are interviewed and observed to gather primary data. and literature uses secondary data. According to the findings of the environmental observations and interviews, the leader was successful in inspiring the group's members to achieve the group's objectives. The business developments for the first three years following the group's formation show this. Three hundred square meters of land were initially planted as a crop, and by the third year, about ten thousand meters had been planted. Also, the group was able to repay its working capital loan obligation and donate to the community. the study demonstrates the effectiveness of women farmers groups in mitigating food poverty. At times of adversity, group farming programs can be a cornerstone of business. Islamic agriculture offers a comprehensive and holistic approach to food production that is rooted in Islamic values and principles. It seeks to promote sustainable and socially responsible farming practices that support the well-being of people, animals, and the environment.